Accuracy of Dose-Saving Artificial-Intelligence-Based 3D Angiography (3DA) for Grading of Intracranial Artery Stenoses: Preliminary Findings - Lang, Stefan; Hölter, Philip; Schmidt, Manuel; Mrochen, Anne; Kuramatsu, Joji; Kaethner, Christian; Roser, Philipp; Kowarschik, Markus; Dörfler, Arnd (Diagnostics, 2023)
Background and purpose: Based on artificial intelligence (AI), 3D angiography (3DA) is a novel postprocessing algorithm for “DSA-like” 3D imaging of cerebral vasculature. Because 3DA requires neither mask runs nor digital subtraction as the current standard 3D-DSA does, it has the potential to cut the patient dose by 50%. The object was to evaluate 3DA’s diagnostic value for visualization of intracranial artery stenoses (IAS) compared to 3D-DSA. Materials and methods: 3D-DSA datasets of IAS (nIAS = 10) were postprocessed using conventional and prototype software (Siemens Healthineers AG, Erlangen, Germany). Matching reconstructions were assessed by two experienced neuroradiologists in consensus reading, considering image quality (IQ), vessel diameters (VD1/2), vessel-geometry index (VGI = VD1/VD2), and specific qualitative/quantitative parameters of IAS (e.g., location, visual IAS grading [low-/medium-/high-grade] and intra-/poststenotic diameters [dintra-/poststenotic in mm]). Using the NASCET criteria, the percentual degree of luminal restriction was calculated. Results: In total, 20 angiographic 3D volumes (n3DA = 10; n3D-DSA = 10) were successfully reconstructed with equivalent IQ. Assessment of the vessel geometry in 3DA datasets did not differ significantly from 3D-DSA (VD1: r = 0.994, p = 0.0001; VD2:r = 0.994, p = 0.0001; VGI: r = 0.899, p = 0.0001). Qualitative analysis of IAS location (3DA/3D-DSA:nICA/C4 = 1, nICA/C7 = 1, nMCA/M1 = 4, nVA/V4 = 2, nBA = 2) and the visual IAS grading (3DA/3D-DSA:nlow-grade = 3, nmedium-grade = 5, nhigh-grade = 2) revealed identical results for 3DA and 3D-DSA, respectively. Quantitative IAS assessment showed a strong correlation regarding intra-/poststenotic diameters (rdintrastenotic = 0.995, pdintrastenotic = 0.0001; rdpoststenotic = 0.995, pdpoststenotic = 0.0001) and the percentual degree of luminal restriction (rNASCET 3DA = 0.981; pNASCET 3DA = 0.0001). Conclusions: The AI-based 3DA is a resilient algorithm for the visualization of IAS and shows comparable results to 3D-DSA. Hence, 3DA is a promising new method that allows a considerable patient-dose reduction, and its clinical implementation would be highly desirable.
CRIS-Team Scopus Importer:2023-03-10
Keywords: 3D angiography; artificial intelligence; deep learning; dose reduction; flat-detector computed tomography (FD-CT); innovative postprocessing; intracranial artery stenosis

Acute Stroke With Large Vessel Occlusion and Minor Clinical Deficits: Prognostic Factors and Therapeutic Implications - Volbers, Bastian; Gröger, Rebecca; Engelhorn, Tobias; Marsch, Armin; Macha, Kosmas; Schwab, Stefan; Dörfler, Arnd; Lang, Stefan; Kallmünzer, Bernd (Frontiers in Neurology, 2021)
Background and Purpose: The optimal acute management of patients with large vessel occlusion (LVO) and minor clinical deficits on admission [National Institutes of Health Stroke Scale (NIHSS) <= 4] remains to be elucidated. The aim of the present study was to investigate the prognostic factors and therapeutic management of those patients.
CRIS-Team WoS Importer:2021-11-19

Association of non-contrast CT markers with long-term functional outcome in deep intracerebral hemorrhage. - Kölbl, Kathrin; Hock, Stefan; Xu, Mingming; Sembill, Jochen; Mrochen, Anne; Balk, Stefanie; Lang, Stefan; Volbers, Bastian; Engelhorn, Tobias Martin; Kallmünzer, Bernd; Kuramatsu, Joji (Frontiers in Neurology, 2024)
OBJECTIVE: Hematoma expansion (HE) is the most important therapeutic target during acute care of patients with intracerebral hemorrhage (ICH). Imaging biomarkers such as non-contrast CT (NCCT) markers have been associated with increasing risk for HE. The aim of the present study was to evaluate the influence of NCCT markers with functional long-term outcome and with HE in patients with deep (basal ganglia and thalamus) ICH who represent an important subgroup of patients at the highest risk for functional deterioration with HE due to the eloquence of the affected brain region. METHODS: From our prospective institutional database, all patients maximally treated with deep ICH were included and retrospectively analyzed. NCCT markers were recorded at diagnostic imaging, ICH volume characteristics were volumetrically evaluated, and all patients received follow-up imaging within 0-48 h. We explored associations of NCCT makers with unfavorable functional outcome, defined as modified Rankin scale 4-6, after 12 months and with HE. Bias and confounding were addressed by multivariable regression modeling. RESULTS: In 322 patients with deep ICH, NCCT markers were distributed as follows: irregular shape: 69.6%, heterogenous density: 55.9%, hypodensities: 52.5%, island sign: 19.3%, black hole sign: 11.5%, and blend sign: 4.7%. Upon multivariable regression analyses, independent associations were documented with the functional outcome for irregular shape (aOR: 2.73, 95%CI: 1.42-5.22, p = 0.002), heterogenous density (aOR: 2.62, 95%CI: 1.40-4.90, p = 0.003) and island sign (aOR: 2.54, 95%CI: 1.05-6.14, p = 0.038), and with HE for heterogenous density (aOR: 5.01, 95%CI: 1.93-13.05, p = 0.001) and hypodensities (aOR: 3.75, 95%CI: 1.63-8.62, p = 0.002). CONCLUSION: NCCT markers are frequent in deep ICH patients and provide important clinical implications. Specifically, markers defined by diverging intra-hematomal densities provided associations with a 5-times higher risk for HE and a 2.5-times higher likelihood for unfavorable functional long-term outcome. Hence, these markers allow the identification of patients with deep ICH at high risk for clinical deterioration due to HE.
EVALuna2:552372

Change your Angle of View Sinusoidal C-Arm Movement in Cranial Flat-panel CT to Improve Image Quality - Lücking, Hannes; Hölter, Philip; Lang, Stefan; Schmidt, Manuel; Eisenhut, Felix; Dörfler, Arnd (Clinical Neuroradiology, 2022)
Background Artifacts from surrounding bony structures, especially from the petrous bones, regularly impair soft tissue computed tomography (CT) imaging of the middle and posterior fossa. This affects flat-panel CT in particular. Sinusoidal movement of the C-arm during acquisition (i.e. craniocaudal tilting along with semicircular rotation) is supposed to reduce artifacts, thus enhancing soft tissue imaging quality. Methods In the work-up of ischemic stroke or subarachnoid hemorrhage 40 patients underwent multi-slice CT (MS-CT) and either plain circular (cFP-CT; n = 20) or sinusoidal (sFP-CT; n = 20) flat-panel CT within a short interval. Two independent readers analyzed MS-CT and FP-CT datasets for recognizability of eight different brain structures and three typical types of artifacts according to a predetermined score. Results Interrater reliability was moderate for cFP-CT (kappa = 0.575) and good to very good for ratings of MS-CT and sFP-CT (kappa = 0.651 to kappa = 1). MS-CT was rated to be significantly better than cFP-CT and sFP-CT (p < 0.0001) in the overall score. Yet, sFP-CT was rated to be significantly superior to cFP-CT (overall p < 0.0001) regarding most anatomical regions and petrous bone artifacts. Conclusion Compared to a standard circular protocol, sinusoidal C-arm movement in cranial FP-CT can significantly reduce artifacts in the posterior fossa and, moreover, can improve visualization of most supratentorial and infratentorial anatomical structures.
CRIS-Team WoS Importer:2022-05-20

Clinical Comparison of FD-CT and MS-CT in Aneurysmal Subarachnoid Haemorrhage: A Single Center Experience - Eisenhut, Felix; Heidelbach, Cornelius; Heynold, Elisabeth; Manhart, Michael; Struffert, Tobias; Brandner, Sebastian; Dörfler, Arnd; Lang, Stefan (Diagnostics, 2022)
Single-center comparison of postinterventional multislice computed tomography (MS-CT) and flat-detector computed tomography (FD-CT) in patients with subarachnoid haemorrhage (SAH) and endovascularly treated cerebral aneurysms with a focus on detection of posttherapeutical complications. Patients with endovascularly treated aneurysmal SAH undergoing both MS-CT and FD-CT within 24 h after intervention were included. Datasets were compared regarding image quality (IQ) as well as qualitative (detection of SAH, intracerebral haemorrhage [ICH], intraventricular haemorrhage [IVH], external ventricular drain [EVD] position, acute obstructive hydrocephalus [AOH]) and quantitative (cella media distance [CMD], modified Graeb score [GS]) parameters. 410 patients with endovascularly treated aneurysmal SAH were included. IQ was equal between MS-CT and FD-CT. FD-CT allowed equal detection of SAH and ICH in comparison to MS-CT. FD-CT allowed excellent detection of IVH and delineation of EVD position with strong agreement to MS-CT findings. FD-CT allowed equal detection of AOH in comparison to MS-CT. There was no significant difference of CMD and GS between FD-CT and MS-CT. Postinterventional FD-CT yields equivalent diagnostic value in patients with endovascular treated SAH as MS-CT. Enabling reliable detection of SAH-associated complications within the angiosuite, FD-CT might be an efficient and safe imaging modality in these clinical emergencies.
CRIS-Team Scopus Importer:2022-11-04
Keywords: cerebral aneurysm; endovascular treatment; flat-detector computed tomography; multislice computed tomography; subarachnoid haemorrhage

Clinical Evaluation of an Innovative Metal-Artifact-Reduction Algorithm in FD-CT Angiography in Cerebral Aneurysms Treated by Endovascular Coiling or Surgical Clipping - Eisenhut, Felix; Schmidt, Manuel; Kalik, Alexander; Struffert, Tobias; Feulner, Julian; Schlaffer, Sven-Martin; Manhart, Michael; Dörfler, Arnd; Lang, Stefan (Diagnostics, 2022)
Treated cerebral aneurysms (IA) require follow-up imaging to ensure occlusion. Metal artifacts complicate radiologic assessment. Our aim was to evaluate an innovative metal-artifact-reduction (iMAR) algorithm for flat-detector computed tomography angiography (FD-CTA) regarding image quality (IQ) and detection of aneurysm residua/reperfusion in comparison to 2D digital subtraction angiography (DSA). Patients with IAs treated by endovascular coiling or clipping underwent both FD-CTA and DSA. FD-CTA datasets were postprocessed with/without iMAR algorithm (MAR+/MAR−). Evaluation of all FD-CTA and DSA datasets regarding qualitative (IQ, MAR) and quantitative (coil package diameter/CPD) parameters was performed. Aneurysm occlusion was assessed for each dataset and compared to DSA findings. In total, 40 IAs were analyzed (ncoiling = 24; nclipping = 16). All iMAR+ datasets demonstrated significantly better IQ (pIQ coiling < 0.0001; pIQ clipping < 0.0001). iMAR significantly reduced the metal-artifact burden but did not affect the CPD. iMAR significantly improved the detection of aneurysm residua/reperfusion with excellent agreement with DSA (naneurysm detection MAR+/MAR−/DSA = 22/1/26). The iMAR algorithm significantly improves IQ by effective reduction of metal artifacts in FD-CTA datasets. The proposed algorithm enables reliable detection of aneurysm residua/reperfusion with good agreement to DSA. Thus, iMAR can help to reduce the need for invasive follow-up in treated IAs.
CRIS-Team Scopus Importer:2022-05-27
Keywords: cerebral aneurysm; endovascular coiling; flat-detector computed tomography angiography; metal-artifact-reduction algorithm; surgical clipping

Detektion einer in der Standard-Mehrzeilen-CT nicht abgrenzbaren Felsenbeinquerfraktur mittels Flachdetektor-CT: ein Fallbericht - Eisenhut, Felix; Wiesmüller, Marco; Lang, Stefan; Taha, Lava (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2022)
CRIS-Team Scopus Importer:2022-08-05

Easy detection of MS-CT-invisible temporal bone fracture via FD-CT: a case report - Eisenhut, Felix; Taha, Lava; Wiesmüller, Marco; Lang, Stefan (Laryngo-Rhino-Otologie, 2023)
CRIS-Team WoS Importer:2023-05-19

Extended Multimodal Flat Detector CT Imaging in Acute Ischemic Stroke: A Pilot Study - Hölter, Philip; Lang, Stefan; Beuscher, Vanessa; Kallmünzer, Bernd; Manhart, Michael; Schwab, Stefan; Dörfler, Arnd (Journal of Digital Imaging, 2023)
By using Flat detector computed tomography (FD-CT), a one-stop-shop approach in the diagnostic workup of acute ischemic stroke (AIS) might be achieved. Although information on upstream vessels is warranted, dedicated FD-CT protocols which include the imaging of the cervical vasculature are still lacking. We aimed to prospectively evaluate the implementation of a new multimodal FD-CT protocol including cervical vessel imaging in AIS patients. In total, 16 patients were included in this study. Eight patients with AIS due to large vessel occlusion (LVO) prospectively received a fully multimodal FD-CT imaging, including non-enhanced flat detector computed tomography (NE-FDCT), dynamic perfusion flat detector computed tomography (FD-CTP) and flat detector computed tomography angiography (FD-CTA) including cervical imaging. For comparison of time metrics and image quality, eight AIS patients, which received multimodal CT imaging, were included retrospectively. Although image quality of NE-FDCT and FD-CTA was rated slightly lower than NE-CT and CTA, all FD-CT datasets were of diagnostic quality. Intracerebral hemorrhage exclusion and LVO detection was reliably possible. Median door-to-image time was comparable for the FD-CT group and the control group (CT:30 min, IQR27-58; FD-CT:44.5 min, IQR31-55, p = 0.491). Door-to-groin-puncture time (CT:79.5 min, IQR65-90; FD-CT:59.5 min, IQR51-67; p = 0.016) and image-to-groin-puncture time (CT:44 min, IQR30-50; FD-CT:14 min, IQR12-18; p < 0.001) were significantly shorter, when patients were directly transferred to the angiosuite, where FD-CT took place. Our study indicates that using a new fully multimodal FD-CT approach including imaging of cervical vessels for first-line imaging in AIS patients is feasible and comparable to multimodal CT imaging with substantial potential to streamline the stroke workflow.
CRIS-Team Scopus Importer:2023-02-03
Keywords: Flat Detector Computed Tomography; Interventional; Stroke; Workflow

High-speed flat-detector computed tomography for temporal bone imaging and postoperative control of cochlear implants - Eisenhut, Felix; Manhart, Michael; Thimsen, Vivian; Mantsopoulos, Konstantinos; Iro, Heinrich; Hornung, Joachim; Dörfler, Arnd; Lang, Stefan; Taha, Lava (Neuroradiology, 2022)
Purpose: Flat-detector computed tomography (FD-CT) is the standard for cochlear implant (CI) imaging. FD-CT systems differ in technical characteristics. Our aim was an evaluation of two different FD-CT generations with different protocols and hardware regarding image quality, radiation dose, and scan time. Methods: Two temporal bone specimens (− / + CI = TB0/TB1) were scanned using three different scanners: two FD-CT systems with different scanning protocols (standard FD-CT: 20 s 70 kV, 20 s 109 kV; high-speed FD-CT [HS-FD-CT]: 7 s 109 kV, 9 s 109 kV, 14 s 72 kV) and MS-CT (5 s 120 kV). Acquired datasets were evaluated in consensus reading regarding qualitative and quantitative parameters: addressing CI- and cochlea-specific parameters, cochlea delineation, lamina spiralis ossea visibility, distinction of single CI electrodes, determination of intracochlear implant position, stapes delineation, and mastoidal septation were assessed. Addressing protocol-specific parameters, radiation dose (dose-length-product/DLP), and scan time were assessed. Results: Two HS-FD-CT protocols (14 s/9 s) provide higher or equivalent diagnostic information regarding CI- and cochlea-specific parameters compared to both standard FD-CT protocols. The fastest HS-FD-CT protocol (7 s)—providing inferior diagnostic information compared to all other FD-CT protocols—still exceeds MS-CT. The highest DLP was recorded for the 14 s HS-FD-CT protocol (TB1 = 956 mGycm); the lowest DLPs were recorded for the 7 s HS-FD-CT protocol (TB0 = 188 mGycm) and for MS-CT (TB0 = 138 mGycm), respectively. HS-FD-CT allows a significant reduction of scan time compared to standard FD-CT. Conclusion: High-speed FD-CT improves visualization of temporal bone anatomy and postoperative assessment of CIs by combining excellent image quality, fast scan time, and reasonable radiation exposure.
CRIS-Team Scopus Importer:2022-04-22
Keywords: Anatomy; Cochlear implant; Flat-detector computed tomography; Postoperative control; Temporal bone

Individual participant data analysis comparing acute stroke patients with anterior versus posterior circulation dissections - Zhang, Yanan; Zhang, Yang; Fröhlich, Kilian; Mrochen, Anne; Mühlen, Iris; Lang, Stefan; Lehmann, Sophie; Gerner, Stefan T.; Huttner, Hagen B.; Schwab, Stefan; He, Li; Bobinger, Tobias (Clinical Neurology and Neurosurgery, 2024)
Background: Cervical artery dissection (CAD) is a relevant etiology of transient ischemic attacks and strokes. Several trials explored the significance of specific antithrombotic treatments, i.e. oral anticoagulation (OAC) versus antiplatelet treatment (APT), on recurrent ischemic complications and clinical outcomes. As overall incidence rates of complications were low there is still controversy which antithrombotic treatment should be used. However, up to now there has been no systematic investigation among CAD-patients with ischemic stroke specifically comparing clinical course and outcome of patients with anterior versus posterior CAD. Methods: We performed an individual participant data analysis of patients with CAD and ischemic stroke. Over a five-year period we pooled data from three sites (i.e. West China Hospital, Chengdu, China as well as Erlangen and Giessen University Hospitals, Germany) and enrolled patients with CAD-associated ischemic stroke. Patient demographics, clinical and in-hospital measures as well as radiological data were retrieved from institutional databases. Clinical follow-up was over 6 months and included data on recurrent ischemic strokes and hemorrhages as well as clinical functional outcome assessed by the modified Rankin Scale dichotomized into favourable (mRS=0–2) and unfavourable. Results: A total of 203 patients with CAD were included of which n=112 had anterior and n=91 had posterior CAD. Patients with posterior CAD were younger (46.0 vs. 41.0 y; p<0.001) than patients with anterior CAD and showed less often arterial hypertension. (42.0 % vs. 28.6 %; p<0.048). Antithrombotic treatment with APT and OAC was similarily distributed among patients with anterior and posterior CAD and not significantly differently related to ischemic or hemorrhagic complications during follow-up (all p=n.s.). Main difference between Chinese and German patients were mode of antithrombotic treatment consisting predominantly of APT in China compared to OAC in Germany. Functional outcome overall was good, yet worse in patients with anterior CAD compared to posterior CAD (80.2 % favorable in anterior CAD vs. 92.2 % in posterior CAD (p=0.014). Conclusion: This study provides evidence that anterior and posterior CAD show baseline imbalances regarding age and comorbidity which may affect clinical outcome. There are no signals of superiority or harm of any specific mode of antithrombotic treatment nor relevant discrepancies in clinical outcome among Chinese and German CAD-associated stroke patients.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Acute ischemic stroke; Antiplatelet treatment; Cervical artery dissections; Clinical outcome; Oral anticoagulation

Influence of bundled care treatment on functional outcome in patients with intracerebral hemorrhage - Mrochen, Anne; Song, Yu; Harders, Verena; Sembill, Jochen; Sprügel, Maximilian; Hock, Stefan; Lang, Stefan; Engelhorn, Tobias; Kallmünzer, Bernd; Volbers, Bastian; Kuramatsu, Joji (Frontiers in Neurology, 2024)
Background and aims: General guideline recommendations in patients with intracerebral hemorrhage (ICH) include blood pressure-, temperature- and glucose management. The therapeutic effect of such a “care bundle” (blood pressure lowering, glycemic control, and treatment of pyrexia) on clinical outcomes becomes increasingly established. For the present study, we aimed to investigate associations of strict bundled care treatment (BCT) with clinical outcomes and characterize associations with key outcome effectors such as hematoma enlargement (HE) and peak perihemorrhagic edema (PHE). Methods: We screened consecutive ICH patients (n = 1,322) from the prospective UKER-ICH cohort study. BCT was defined as achieving and maintaining therapeutic ranges for systolic blood pressure (110–160 mmHg), glucose (80–180 mg/dL), and body temperature (35.5–37.5°C) over the first 72 h. The primary outcome was the functional outcome at 12 months (modified Rankin Scale (mRS) 0–3). Secondary outcomes included mortality at 12 months, the occurrence of hematoma enlargement, and the development of peak perihemorrhagic edema. Confounding was addressed by a doubly robust methodology to calculate the absolute treatment effect (ATE) and by calculating e-values. Results: A total of 681 patients remained for analysis, and 182 patients fulfilled all three BCT criteria and were compared to 499 controls. The ATE of BCT to achieve the primary outcome was 9.3%, 95% CI (1.7 to 16.9), p < 0.001; e-value: 3.1, CI (1.8). Mortality at 12 months was significantly reduced by BCT [ATE: −12.8%, 95% CI (−19.8 to −5.7), p < 0.001; e-value: 3.8, CI (2.2)], and no association was observed for HE or peak PHE. Significant drivers of BCT effect on the primary outcome were systolic blood pressure control (ATE: 15.9%) and maintenance of normothermia (ATE: 10.9%). Conclusion: Strict adherence to this “care bundle” over the first 72 h during acute hospital care in patients with ICH was independently associated with improved functional long-term outcome, driven by systolic blood pressure control and maintenance of normothermia. Our findings strongly warrant prospective validation to determine the generalizability especially in Western countries. Clinical trial registration:ClinicalTrials.gov, identifier [ID: NCT03183167].
CRIS-Team Scopus Importer:2024-08-30
Keywords: bundle; HE; ICH; PHE; treatment

Peak Edema Extension Distance: An Edema Measure Independent from Hematoma Volume Associated with Functional Outcome in Intracerebral Hemorrhage - Giede-Jeppe, Antje; Gerner, Stefan T.; Sembill, Jochen; Kuramatsu, Joji; Lang, Stefan; Lücking, Hannes; Staykov, Dimitre; Huttner, Hagen B.; Volbers, Bastian (Neurocritical Care, 2023)
Background: Our objective was to test the association between hematoma volume and long-term (> 72 h) edema extension distance (EED) evolution and the association between peak EED and early EED increase with functional outcome at 3 months in patients with intracerebral hemorrhage (ICH). Methods: This retrospective cohort study included patients with spontaneous supratentorial ICH between January 2006 and January 2014. EED, an edema measure defined as the distance between the hematoma border and the outer edema border, was calculated by using absolute hematoma and edema volumes. We used multivariable logistic regression accounting for age, ICH volume, and location and receiver operating characteristic analysis for assessing measures associated with functional outcome and EED evolution. Functional outcome after 3 months was assessed by using the modified Rankin Scale (0–3 = favorable, 4–6 = unfavorable). To identify properties associated with peak EED multivariable linear and logistic regression analyses were conducted. Results: A total of 292 patients were included. Median age was 70 years (interquartile range [IQR] 62–78), median ICH volume on admission 17.7 mL (IQR 7.9–40.2), median peak perihemorrhagic edema (PHE) volume was 37.5 mL (IQR 19.1–60.6), median peak EED was 0.67 cm (IQR 0.51–0.84) with an early EED increase up to 72 h (EED72–0) of 0.06 cm (− 0.02 to 0.15). Peak EED was found to be independent of ICH volume (R 2 = 0.001, p = 0.6). In multivariable analyses, peak EED (odds ratio 0.224, 95% confidence interval [CI] [0.071–0.705]) and peak PHE volume (odds ratio 0.984 [95% CI 0.973–0.994]) were inversely associated with favorable functional outcome at 3 months. Receiver operating characteristic analysis identified a peak PHE volume of 26.8 mL (area under the curve 0.695 [95% CI 0.632–0.759]; p ≤ 0.001) and a peak EED of 0.58 cm (area under the curve 0.608 [95% CI 0.540–0.676]; p = 0.002) as best predictive values for outcome discrimination. Conclusions: Compared with absolute peak PHE volume, peak EED represents a promising edema measure in patients with ICH that is largely hematoma volume-independent and nevertheless associated with functional outcome.
CRIS-Team Scopus Importer:2023-12-08
Keywords: Early EED increase; Edema; EED; ICH; PHE

Pulsed Arterial Spin Labeling and Segmented Brain Volumetry in the Diagnostic Evaluation of Frontotemporal Dementia, Alzheimer’s Disease and Mild Cognitive Impairment - Marterstock, Dominique; Knott, Michael; Lang, Stefan; Oberstein, Timo; Kornhuber, Johannes; Dörfler, Arnd; Schmidt, Manuel; Hölter, Philip (Tomography, 2022)
Background: Previous studies suggest that brain atrophy can not only be defined by its morphological extent, but also by the cerebral blood flow (CBF) within a certain area of the brain, including white and gray matter. The aim of this study is to investigate known atrophy patterns in different forms of dementia and to compare segmented brain volumetrics and pulsed arterial spin labeling (pASL) data to explore the correlation between brain maps with atrophy and this non-contrast-enhanced brain-perfusion method. Methods: Our study comprised 17 patients with diagnosed cognitive impairment (five Alzheimer’s disease = AD, five frontotemporal dementia = FTD, seven mild cognitive impairment = MCI) and 19 healthy control subjects (CO). All patients and controls underwent 4D-pASL brain-perfusion MR imaging and T1w MPRAGE. The data were assessed regarding relative brain volume on the basis of 286 brain regions, and absolute and relative cerebral blood flow (CBF/rCBF) were derived from pASL data in the corresponding brain regions. Mini-Mental State Examination (MMSE) was performed to assess cognitive functions. Results: FTD patients demonstrated significant brain atrophy in 43 brain regions compared to CO. Patients with MCI showed significant brain atrophy in 18 brain regions compared to CO, whereas AD patients only showed six brain regions with significant brain atrophy compared to CO. There was good correlation of brain atrophy and pASL perfusion data in five brain regions of patients with diagnosed FTD, especially in the superior temporal gyrus (r = 0.900, p = 0.037), the inferior frontal white matter (pars orbitalis; r = 0.968, p = 0.007) and the thalami (r = 0.810, p = 0.015). Patients with MCI demonstrated a correlation in one brain region (left inferior fronto-occipital fasciculus; r = 0.786, p = 0.036), whereas patients with diagnosed AD revealed no correlation. Conclusions: pASL can detect affected brain regions in cognitive impairment and corresponds with brain atrophy, especially for patients suffering from FTD and MCI. However, there was no correlation of perfusion alterations and brain atrophy in AD. pASL perfusion might thus represent a promising tool for noninvasive brain-perfusion evaluation in specific dementia subtypes as a complimentary imaging-based bio marker in addition to brain volumetry.
CRIS-Team Scopus Importer:2022-02-11
Keywords: Alzheimer’s disease; Brain volumetry; Dementia; Frontotemporal dementia; Mild cognitive impairment; Pulsed arterial spin labeling

The anesthetic approach for endovascular recanalization therapy depends on the lesion site in acute ischemic stroke - Fröhlich, Kilian; Siedler, Gabriela; Stoll, Svenja; Macha, Kosmas; Kinfe, Thomas Mehari; Dörfler, Arnd; Eisenhut, Felix; Engelhorn, Tobias; Hölter, Philip; Lang, Stefan; Mühlen, Iris; Schmidt, Manuel; et al. (Neuroradiology, 2021)
Purpose Endovascular therapy (EVT) of large-vessel occlusion in acute ischemic stroke (AIS) may be performed in general anesthesia (GA) or conscious sedation (CS). We intended to determine the contribution of ischemic cerebral lesion sites on the physician's decision between GA and CS using voxel-based lesion symptom mapping (VLSM). Methods In a prospective local database, we sought patients with documented AIS and EVT. Age, stroke severity, lesion volume, vigilance, and aphasia scores were compared between EVT patients with GA and CS. The ischemic lesions were analyzed on CT or MRI scans and transformed into stereotaxic space. We determined the lesion overlap and assessed whether GA or CS is associated with specific cerebral lesion sites using the voxel-wise Liebermeister test. Results One hundred seventy-nine patients with AIS and EVT were included in the analysis. The VLSM analysis yielded associations between GA and ischemic lesions in the left hemispheric middle cerebral artery territory and posterior circulation areas. Stroke severity and lesion volume were significantly higher in the GA group. The prevalence of aphasia and aphasia severity was significantly higher and parameters of vigilance lower in the GA group. Conclusions The VLSM analysis showed associations between GA and ischemic lesions in the left hemispheric middle cerebral artery territory and posterior circulation areas including the thalamus that are known to cause neurologic deficits, such as aphasia or compromised vigilance, in AIS-patients with EVT. Our data suggest that higher disability, clinical impairment due to neurological deficits like aphasia, or reduced alertness of affected patients may influence the physician's decision on using GA in EVT.
CRIS-Team WoS Importer:2021-07-23

The influence of liver dysfunction (LD) on functional outcome in intracerebral hemorrhage - Beuscher, Vanessa; Sprügel, Maximilian; Mrochen, Anne; Hölter, Philip; Lang, Stefan; Kuramatsu, Joji; Huttner, Hagen (Journal für Anasthesie und Intensivbehandlung, 2021)
CRIS-Team Scopus Importer:2024-12-16

Thrombocytopenia and Clinical Outcomes in Intracerebral Hemorrhage: A Retrospective Multicenter Cohort Study - Mrochen, Anne; Sprügel, Maximilian; Gerner, Stefan; Sembill, Jochen; Lang, Stefan; Lücking, Hannes; Kuramatsu, Joji; Huttner, Hagen (Stroke, 2021)
BACKGROUND AND PURPOSE: The impact of platelets on hematoma enlargement (HE) of intracerebral hemorrhage (ICH) is not yet sufficiently elucidated. Especially the role of reduced platelet counts on HE and clinical outcomes is still poorly understood. This study investigated the influence of thrombocytopenia on HE, functional outcome, and mortality in patients with ICH with or without prior antiplatelet therapy (APT). METHODS: Individual participant data of multicenter cohort studies (multicenter RETRACE program [German-Wide Multicenter Analysis of Oral Anticoagulation-Associated Intracerebral Hemorrhage] and single-center UKER-ICH registry [Universitätsklinikum Erlangen Cohort of Patients With Spontaneous ICH]) were grouped into APT and non-APT ICH patients according to the platelet count, that is, with or without thrombocytopenia (cells <150×109/L). Of all patients, 51.5% (1124 of 2183) were on vitamin K antagonist. Imbalances in baseline characteristics including proportions of vitamin K antagonist patients were addressed using propensity score matching. Outcome analyses included HE (>33%), as well as mortality and functional outcome, after 3 months using the modified Rankin Scale, dichotomized into favorable (modified Rankin Scale score, 0-3) and unfavorable (modified Rankin Scale score, 4-6). RESULTS: Of overall 2252 ICH patients, 11.4% (52 of 458) under APT and 14.0% (242 of 1725) without APT presented with thrombocytopenia on admission. The proportion of patients with HE was not significantly different between patients with or without thrombocytopenia among APT and non-APT ICH patients after propensity score matching (HE: APT patients: 9 of 40 [22.5%] thrombocytopenia versus 27 of 115 [23.5%] nonthrombocytopenia, P=0.89; non-APT patients: 54 of 174 [31.0%] thrombocytopenia versus 106 of 356 [29.8%] nonthrombocytopenia, P=0.77). In both (APT and non-APT) propensity score matching cohorts, there were no significant differences regarding functional outcome. Mortality after 3 months did not differ among non-APT patients, whereas the mortality rate was significantly higher for APT patients with thrombocytopenia versus APT patients with normal platelet count (APT: 29 of 46 [63.0%] thrombocytopenia versus 58 of 140 [41.4%] nonthrombocytopenia, P=0.01; non-APT: 95 of 227 [41.9%] thrombocytopenia versus 178 of 455 [39.1%] nonthrombocytopenia, P=0.49). CONCLUSIONS: Our study implies that thrombocytopenia does not affect rates of HE and functional outcome among ICH patients, neither in patients with nor without APT. In light of increased mortality, the significance of platelet transfusions for ICH patients with thrombocytopenia and previous APT should be explored in future studies.
CRIS-Team Scopus Importer:2021-04-19
Keywords: cohort studies; hematoma enlargement; intracerebral hemorrhage; platelet count; thrombocytopenia

"Virtual stent" - clinical evaluation and user experience of on-the-fly stent simulation in treatment of cerebral aneurysms - Lücking, Hannes; Birkhold, Annette; Hölter, Philip; Lang, Stefan; Gölitz, Philipp; Schmidt, Manuel; Mrochen, Anne; Brandner, Sebastian; Dörfler, Arnd (Interventional Neuroradiology, 2021)
Background Predicting final stent position can be challenging when treating cerebral aneurysms. Third-Party software proved helpful in selecting proper stents in treatment planning. Recent angiographic systems provide basic stent simulation capabilities integrated in the post-processing software to simulate stent position. Goal of this analysis was to evaluate the simulation process and correlation with definite stent position. Materials and Methods Thirty-three datasets with fusiform (n = 10) and saccular (n = 23) aneurysms, treated with stent or flow-diverter, were processed. A "virtual stent" of the same (nominal) size was simulated and its position was compared to the treatment result. Simulated length was rated in five grades (too short, shorter, equal, longer, too long), with regard to side-branches, anchoring zone etc. Simulation quality (centerline recognition/adherence to vessel margins) was rated in three grades (no, minor or major corrections required). Results Simulation was successful in 32/33 cases (97%), with one abortive attempt (3%). In 27/33 simulations (82%), there was no need for centerline refinement. Minor corrections were necessary in four and major corrections in two cases. Simulated nominal length was rated "equal" in 14/33 (42%) cases and "shorter" or "longer" - but within acceptable range - in each 9/33 (27%) cases. Conclusion Basic stent simulation tools available with genuine angiographic workplace software can provide good simulation capabilities without need for third-party equipment. They can facilitate treatment planning and help to avoid shortage of devices. Yet, lack of calculation of foreshortening in large vessel diameters leaves the user to rely on their experience to account for device-specific properties.
CRIS-Team WoS Importer:2021-11-12